On Optimal Hardy Inequalities in Cones - Baptiste Devyver; Yehuda Pinchover; Georgios Psaradakis (Bruno Pini Mathematical Analysis Seminar, 2014)
For a given subcritical Schrödinger operator in a cone in ℝn with a given Hardy potential corresponding to the distance to the boundary of the cone, we present an explicit optimal Hardy-type improvement. In particular, we present an explicit expression for the associate best Hardy constant, and for the corresponding ground state.